Protective effect of peonidin - anthocyanidin class flavonoid against doxorubicin-induced toxicity in H9C2 cardiomyoblast cell lines - Namathoti, Jyothirmai; Pasupula, Rajeshwari (Creative Pharma Assent, 2025)
Background: This study investigates the cardioprotective properties of peonidin against cytotoxicity induced by doxorubicin (DOX) in H9c2 cardiomyocytes using both in vitro and in silico methods. H9c2 cells were exposed to DOX alone as well as in combination with different concentrations of peonidin for various time durations. Methodology: Cytoprotection was studied using MTT assay for viability, LDH leakage, SOD activity, lipid peroxidation, and ROS content. Furthermore, molecular docking was also performed to analyze the binding affinity of peonidin with angiotensin-converting enzyme (ACE) and endothelin-converting enzyme-1 (ECE-1), utilizing captopril as a control. Results and Discussion: DOX drastically inhibited cell viability, whereas peonidin co-treatment maintained it dose dependently, restoring it to 99.74% at 150 µg/mL after 72 h. LDH release through DOX-triggered membrane disruption was alleviated from 175.84% to 78.40% by peonidin. ROS levels were also decreased from 191.13% (DOX) to 61.29% by peonidin, reflecting robust antioxidant activity. Lipid peroxidation was strongly inhibited, and SOD activity, decreased by DOX (36.59±0.306 AU), was restored close to control levels (97.85±0.313 AU) by peonidin. Docking studies indicated that peonidin exhibited a superior binding affinity with ACE (-95.72 kcal/mol) and ECE-1 (-78.08 kcal/mol) compared to captopril, characterized by good van der Waals and hydrogen bonding interactions. Conclusion: Peonidin potently mitigates DOX-induced oxidative injury in cardiomyocytes, showing great promise as a natural cardioprotective agent, as evidenced by both biochemical assays and molecular docking studies against ACE and ECE-1.